1986
DOI: 10.2307/1939824
|View full text |Cite
|
Sign up to set email alerts
|

Soil Properties of Steep Appalachian Old Fields

Abstract: Shifting cultivation of com (Zea mays) was widely practiced on steep, mesic slopes in the Appalachian Mountains during the period 1800-1930. Contemporary reports often emphasized both the severity of erosion during the period of cultivation, and the rapidity of reforestation following abandonment of agriculture. In eastern Kentucky, old fields that originated during this period are presently occupied by nearly pure yellow-poplar (Liriodendron tulipifera) stands that contrast with the mixed mesophytic forests f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
2

Year Published

1989
1989
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 38 publications
3
29
2
Order By: Relevance
“…If litter inputs correspond linearly to tree abundance, then plant tissue from tulip poplar alone would comprise a majority of the organic matter in the forest floor of previous pastures. This may contribute not only to the low variability in C and N concentrations at fine scales, but also to the local reduction in mineral soil Ca variability, because tulip poplar concentrates Ca in its leaves (Coile 1937, Kalisz 1986, and trees that pump Ca from the deep soil can sustain high amounts of available Ca in the surface soil (Dijkstra and Smits 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If litter inputs correspond linearly to tree abundance, then plant tissue from tulip poplar alone would comprise a majority of the organic matter in the forest floor of previous pastures. This may contribute not only to the low variability in C and N concentrations at fine scales, but also to the local reduction in mineral soil Ca variability, because tulip poplar concentrates Ca in its leaves (Coile 1937, Kalisz 1986, and trees that pump Ca from the deep soil can sustain high amounts of available Ca in the surface soil (Dijkstra and Smits 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, the deposition of excreta may enhance the heterogeneity of those nutrients that are abundant in manure, such as P, K, and Mg (Afzal and Adams 1992, Augustine and Frank 2001, Augustine 2003. Changes in tree community composition following land abandonment may also influence the spatial distribution of soil nutrients, especially those such as C, N, and calcium (Ca), which are closely associated with litter inputs (Melillo et al 1982, Kalisz 1986, Dijkstra and Smits 2002. Pastures and logged stands may consequently exhibit similar levels of C, N, and Ca variability and different levels of P, potassium (K), and magnesium (Mg) variability.…”
Section: Introductionmentioning
confidence: 99%
“…Recent forest soils may continue to reflect their agricultural history over 100 years after reforestation (Koerner et al 1997;Verheyen et al 1999;Dupouey et al 2002). Alternatively, as an equal number of studies have found, they may become broadly similar to ancient forest soils within that time (Kalisz 1986;Compton and Boone 2000;Flinn et al 2005). This regional variation can be difficult to predict because it depends on complex interactions between inherent soil fertility, the nature and duration of agricultural use, and time since abandonment.…”
Section: Environmental Characterizationsmentioning
confidence: 99%
“…By comparison, nonfertilized agricultural plots typically produce less than 2 Mg biomass ha À1 year À1 ; while productivity on fertilized agricultural sites is higher, it rarely reaches 50% of that observed on forested sites (Figure 2 Below-ground carbon on forest sites is largely contained in coarse roots and stumps. The majority of this stock is lost in the first few decades after sites are converted to agricultural use as soil carbon losses exceed carbon inputs (Bolstad and Vose 2004;Harris et al 1977;Kalisz 1986). Soil temperatures increase, accelerating below-ground decomposition of existing carbon stocks as forest cover and its deadfall and litter inputs are reduced.…”
Section: Terrestrial Ecosystemsmentioning
confidence: 99%